Proceedings of International Conference on ICT for Sustainable Development ICT4SD 2015 Volume 2 - Satapathy, Suresh Chandra; Joshi, Amit.; Modi, Nilesh; Pathak, Nisarg; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The two volumes of this book collect high-quality peer-reviewed research papers presented in the International Conference on ICT for Sustainable Development (ICT4SD 2015) held at Ahmedabad, India during 3 - 4 July 2015. The book discusses all areas of Information and Communication Technologies and its applications in field for engineering and management. The main focus of the volumes are on applications of ICT for Infrastructure, e-Governance, and contemporary technologies advancements on Data Mining, Security, Computer Graphics, etc. The objective of this International Conference is to provide an opportunity for the researchers, academicians, industry persons and students to interact and exchange ideas, experience and expertise in the current trend and strategies for Information and Communication Technologies.
Chapter 1. Implementing the Logical Security Framework for E-commerce Based on Service Oriented Architecture -- Chapter 2. Indian Sign Language Translator Using Kinect -- Chapter 3. Formal Transformation of UML Diagram: Use Case, Class, Sequence Diagram with Z Notation for Representing the Static & Dynamic Perspectives of System -- Chapter 4. A Survey of Android Malware Detection Strategy and Techniques -- Chapter 5. A Review on Dynamic View Selection -- Chapter 6. Software Project Estimation Using Fuzzy Inference System -- Chapter 7. Linear and Non Linear Modeling of Protein Kinase B/AkT -- Chapter 8. Lost Connectivity Restoration in Partitioned Wireless Sensor Networks -- Chapter 9. Analysis of Authentication Techniques Adopted by End Users in Real Life Cloud Implementation -- Chapter 10. Network Analysis of ICMP Ping Flood DoS Attack in Wi-Max and Wireless LAN -- Chapter 11. Scheduling in Big Data Heterogeneous Distributed System Using Hadoop -- Chapter 12. A New Differential Scan-Based Side-Channel Attacks against RSA Cryptosystem -- Chapter 13. Grey Wolf Optimizer (GWO) algorithm for minimum weight planer frame design subjected to AISC-LRFD -- Chapter 14. Child Growth Mentor - A Proposed Model for Effective Use of Mobile Application for Better Growth of Child -- Chapter 15. Design & Development of a Rule Based Urdu Lemmatizer -- Chapter 16. Enhanced Microstrip Patch Antenna Using Metamaterial for DECT and Aircraft Wireless System Applications -- Chapter 17. An Enhanced Strategy to Minimize Makespan in Cloud Environment to Accelerate the Performance -- Chapter 18. Prefix Length Based Disjoint Set Tries For IPv6 Lookup -- Chapter 19. Implementation of FAST Clustering-based Feature Subset Selection Algorithm for High-Dimensional Data -- Chapter 20. Performance Comparison of 2D and 3D Zigbee Wireless SensorNetworks -- Chapter 21. Enhancement of Data Security by PMK Technique -- Chapter 22. Privacy-Leveled Perturbation Model for Privacy Preserving Collaborative Data Mining -- Chapter 23. Extended Bellman Ford Algorithm with Optimized Time of Computation -- Chapter 24. Supervised Link Prediction using Forecasting Models on Weighted Online Social Network -- Chapter 25. Dual Band Rectangular Shape Antenna With Sideway Extension at Top and Bottom for WLAN and WiMax Application -- Chapter 26. A Framework to Rank Nodes in Social Media Graph Based on Sentiment Related Parameters -- Chapter 27. Development of Analytical method to determine the deflection of tapered cantilever beam with inclined loading condition using software simulation -- Chapter 28. Bio-Inspired Ultra Low Power Design of comparator with Noise Compensation using Hysteresis technique designed for Biomedical Engineering (Pacemaker) -- Chapter 29. Comparative Analysis of Different Architectures of MCML Square Root Carry Select Adders for Low Power Applications -- Chapter 30. Improvement in Quality of Extractive Text Summaries using Modified Reciprocal Ranking -- Chapter 31. A Novel Compact Monopole Multiband Antenna for WiMAX/Satellite/Military Applications -- Chapter 32. Critical Study and Analysis of Cyber Law Awareness amongst the Netizens -- Chapter 33. Information Communication Technologies for Research and Academic Development -- Chapter 34. An Insider Cyber Threat Prediction Mechanism based on Behavioral Analysis -- Chapter 35. Enhancing Amplifier characteristics using Quantum dots -- Chapter 36. An Approach to Secure Internet of Things against DDoS -- Chapter 37. Issues in Quantitative Association Rule Mining: A Big Data Perspective -- Chapter 38. A Framework for temporal information search and exploration -- Chapter 39. Item Amalgamation Approach for SerendipityOriented Recommender System -- Chapter 40. A Two Stage Integrated Approach of DNA Cryptography -- Chapter 41. ADVANCED IRRIGATION SYSTEMS IMPACTING SUSTAINABILITY AND REDUCING WATER NEEDS - ROLE OF ICT IN IRRIGATION -- Chapter 42. Parallelization of Load Flow Analysis -- Chapter 43. Hierarchical Role-Based Access Control with Homomorphic Encryption for Database as a Service -- Chapter 44. Hybrid Miner Tracking System at 2.4GHz for Underground Mines -- <Chapter 45. PARTITION BASED FREQUENT CLOSED PATTERN MINER -- Chapter 46. A Study On Working Of Ad Auctioning by Google AdWords -- Chapter 47. A Novel Approach for Polarity Determination Using Emoticons: Emoticon-Graph -- Chapter 48. Scheduling for Distributed Applications in Mobile Cloud Computing -- Chapter 49. High Availability of Databases for Cloud -- Chapter 50. Customized Parameter Configuration Framework for Performance Tuning in Apache Hadoop -- Chapter 51. Hand Skin Classification from Other Skin Objects Using Multi-Direction 3D Color-Texture Feature & Cascaded Neural Network Classifier -- Chapter 52. Texture Features for the Detection of Acute Lymphoblastic Leukemia -- Chapter 53. Design and Implementation of Non Touch Enable Password System -- Chapter 54. Intelligent Web Security Testing with Threat Assessment and Client Server Penetration Using Burp Suite -- Chapter 55. QoS-aware Autonomic Cloud Computing for ICT -- Chapter 56. Emerging Green ICT: Heart Disease Prediction Model in Cloud Environment -- Chapter 57. Energy Conscious Allocation and Scheduling of Tasks in ICT Cloud Paradigm -- Chapter 58. Controlling of FPGA Based Optical Polarimeter Using LabVIEW -- Chapter 59. Automatic Intelligent Traffic Controlling for Emergency Vehicle Rescuing -- Chapter 60. A Capacity Constraint Distributed Data Dissemination Protocol for Ad-hoc Cognitive Radio Networks -- Chapter 61. Enhancing Performance of Security Log Analysis Using Correlation-Prediction Technique -- Chapter 62. Differential Weight Based Hybrid Approach to Detect Software Plagiarism -- Chapter 63. Selecting Favorable Reference Nodes to aid Localization in Wireless Sensor Networks -- Chapter 64. A Scientometric Analysis of Smart Grid Implementation at Distribution Feeder -- Chapter 65. Enhancing Web Search Results Using Aggregated Search -- Chapter 66. Managing Heterogeneity by Synthesizing Composite Data -- Chapter 67. A Novel Approach to Filter Topic Related Important Terms within Document -- Chapter 68. Domain Driven Density Based Clustering Algorithm -- Chapter 69. Adoptive Approach of AODV and DSDV Routing Protocols using Optimal Probabilistic Logical Key Hierarchy in MANET -- Chapter 70. Re-Clustering Approach Using WCA in AODV and DSDV Routing Protocols in MANET.-Chapter 71. Issues and Challenges of Heterogeneous Datasets in Map Reduce framework of Big Data Environment -- Chapter 72. Strong Virtual Password Scheme Using Reference Switching on Coded User Parameters and Phishing Attack -- Chapter 73. Need Of ICT For Sustainable Development In Petroleum Industry -- Chapter 74. Hybrid K-mean and Refinement Based on Ant for Color Image Clustering -- Chapter 75. A Framework for Secure Data Storage in Mobile Cloud Computing -- Chapter 76. Hindi Word Sense Disambiguation Using Cosine Similarity -- Chapter 77. A Multi-Classifiers Based Novel DoS/DDoS Attack Detection Using Fuzzy Logic. .
Keywords: Computational intelligence; Data mining; Computer-aided engineering; Telecommunication; Technological innovations; Computational Intelligence; Data Mining and Knowledge Discovery; Computer-Aided Engineering (CAD, CAE) and Design; Communications Engineering, Networks; Innovation and Technology Management